Frontispiece: Stereo‐ and Regioselective Synthesis of Tricyclic Spirolactones by Diastereoisomeric Differentiation of a Collective Key Precursor. Issue 8 (11th February 2016) - Valerio, Viviana; Mostinski, Yelena; Kotikalapudi, Ramesh; Tsvelikhovsky, Dmitry
Abstract : Diastereomeric Differentiation In their Full Paper onpage 2640 ff., D. Tsvelikhovsky et al. describe a general, parallel, and collective synthesis of tricyclic spirolactones by controlled cyclizations of easily accessible common key precursors. The rapid composition of the key cycloalkylmethylene unit yields an assembly of bicyclic diastereomeric iodolactones, which are individually converted into a wide range of tricyclic angularly fused lactones in a regioselective and stereodirected fashion by diastereomeric differentiation of collective key precursor.